Diskursus Ekonomi Islam Modern dan Kritik Terhadapnya - Fajar Syarif (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
This article focuses on the economic discourse of Islam and criticism for it. The main reason for this focus is to explain the historical development of modern Islamic economics, some definitions and the current of Islamic economics and also the economic criticism of Islam. Islamic economics as a superior system, because it has character and fixed all the time. Islamic economic is a system, because it comes on of al-Quran and al-Sunnah. The economic system committed to realizing the social implementation of social responsibility. Islamic economics today has presented a new social and ethical meaning, but it is also a factor institutionalism and sociological thinking. The rise of modern economic study at least suggests two things. First, there are doubts about the ability of the economic system that is applied during this time. Secondly, the awareness of the need for excavation of alternative economic systems, especially those derived from the values of Islam, a religion which is the doctrines are very comprehensive.